2022
DOI: 10.1186/s12913-022-08554-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient experiences with a telehealth approach for the PRO-ACTIVE trial intervention in head and neck cancer patients

Abstract: Introduction Following the COVID-19 directive to cease non-essential services, a rapid shift was made in the delivery of Speech Language Pathology (SLP) dysphagia management in the 3-arm, randomized PRO-ACTIVE trial. To inform future programs, this study explored patients’ experiences with telehealth when the planned in-person SLP intervention was moved to a telehealth modality. Methods A theory-guided qualitative descriptive approach was used. Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Survey responses indicated that overall, participants were satisfied with their telehealth appointments and were willing to accept this model of working into HNC pathways. These findings are in keeping with other studies exploring patient experience of telehealth in SLT services (Burns et al, 2012;Khan et al, 2022;Weidner & Lowman, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Survey responses indicated that overall, participants were satisfied with their telehealth appointments and were willing to accept this model of working into HNC pathways. These findings are in keeping with other studies exploring patient experience of telehealth in SLT services (Burns et al, 2012;Khan et al, 2022;Weidner & Lowman, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Telehealth has also been received positively by participants in SLT research trials. Khan et al (2022) explored patient experience of the use of telehealth for the PRO-ACTIVE trial intervention during the COVID-19 pandemic. Participants reported that telehealth did not compromise their learning and they described feeling 'satisfied, comfortable and confident' following their sessions.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Notably, with the COVID-19 pandemic resulting in unprecedented telemedicine growth among healthcare organizations, 1-4 many patients may be experiencing their first several telemedicine visits. 30,31 Our study found that allowing patients to have mock telehealth visits was wellreceived, suggesting that improving patient comfort and managing expectations of telehealth may improve the patient experience.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings suggest positive experiences with telehealth for preanesthesia and postoperative visits among patients and caregivers of various cancer types (e.g., gastrointestinal, genitourinary, and gynecologic). Common benefits of telehealth included time and cost savings associated with travel, which have been previously documented in the literature in cancer care 13,16,19,20,22,27–31 . Since surgical recovery can involve fatigue, one surgery‐specific benefit was allowing surgical patients to avoid having to travel while fatigued and in recovery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation